Separation behavior of short single‐ and double‐stranded DNA in 1 micron and 100 nm glass channels. Issue 2 (2nd October 2013) - Russell, Alexander J.; Del, Jackson T.; Wynne, Thomas M.; Napoli, Maria T.; Pennathur, Sumita; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> Micro‐ and nanofluidic lab‐on‐chip technology offers the unique capability of high‐resolution separation, identification, and manipulation of biomolecules with broad applications in chemistry, biology, and medicine. In this work, we probe the effects of ionic strength on separation of ss‐ and dsDNA within 1 micron and 100 nm‐deep glass channels. Separation behavior of DNA is influenced by a number of parameters, including ionic strength, melting temperature, strand length, strand conformation, and channel size. Specifically, we find a shift in the observed mobility of 10‐bp (base pair) dsDNA for different ionic strengths due to changes in kinetic parameters, underlying the importance of these considerations when working with short DNA. For 50‐base DNA, the electrophoretic mobility difference between ss‐ and dsDNA increases as the ionic strength increases due to changes in conformation of the ssDNA. Finally, we find that decreasing channel size decreases the absolute electrophoretic mobility of 10‐ and 20‐bp ss‐ and dsDNA, due to both hydrodyamic confinement and electric double layer (EDL) interactions. We hypothesize that about 4% mobility reduction is due to hydrodynamic confinement, which is observed at all ionic strengths, and further reduction is due to EDL interactions between the DNA and the channel walls, only observed at low ionic strengths.